NOD Signaling and Cell Death - Heim, Valentin J.; Stafford, Che A.; Nachbur, Ueli (Frontiers in Cell and Developmental Biology, 2019)
Innate immune signaling and programmed cell death are intimately linked, and many signaling pathways have the capability to regulate and induce both, transcription of inflammatory mediators, or autonomous cell death. The best characterized examples for these dual outcomes are members of the TNF superfamily, inflammasome receptors as well as the Toll like receptors. These can both initiate the production of immune modulatory messengers, but also induce various forms of programmed cell death. Signaling via the intracellular peptidoglycan receptors NOD1 and NOD2, however, does not appear to follow this trend, despite having signaling proteins, or proteins with domains that are linked to programmed cell death, such as RIP kinases, Inhibitors of Apoptosis proteins or the CARD domains on the NOD receptors. Here we review the latest findings on molecular mechanisms downstream of NOD receptors and explore the links between this immune signaling pathway and the regulation of cell death.